2016
DOI: 10.18632/oncotarget.12333
|View full text |Cite
|
Sign up to set email alerts
|

CARP-1 functional mimetics are novel inhibitors of drug-resistant triple negative breast cancers

Abstract: Doxorubicin and Cisplatin are the frontline therapeutics for treatment of the triple negative breast cancers (TNBCs). Emergence of drug-resistance often contributes to failure of drugs and poor prognosis, and thus necessitates development of new and improved modalities to treat TNBCs. We generated and characterized chemotherapy-resistant TNBC cells following their culture in chronic presence of Doxorubicin or Cisplatin, and tested whether their viabilities were inhibited by a novel class of CARP- 1 functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(53 citation statements)
references
References 38 publications
(81 reference statements)
4
49
0
Order By: Relevance
“…A 4.0μM dose of CFM-4.16 on the other hand provoked ∼80% reduction in the viabilities of all the Everolimus-resistant RCC cells. These data corroborate our current findings in Figure 1 and our recent studies demonstrating increased effectiveness of CFM-4.16 in attenuating viabilities of the parental RCC cells as well as drug-resistant RCC (Figure 2 ) and TNBC cells [ 26 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…A 4.0μM dose of CFM-4.16 on the other hand provoked ∼80% reduction in the viabilities of all the Everolimus-resistant RCC cells. These data corroborate our current findings in Figure 1 and our recent studies demonstrating increased effectiveness of CFM-4.16 in attenuating viabilities of the parental RCC cells as well as drug-resistant RCC (Figure 2 ) and TNBC cells [ 26 ].…”
Section: Resultssupporting
confidence: 93%
“…Our prior findings had indicated anti-cancer properties of a novel class of CFM compounds [ 10 ], and our recent medicinal chemistry-based structure-activity relationship (SAR) studies reported identification of CFM analogs, in particular CFM-4.16, that was a superior inhibitor of parental and drug-resistant human and murine triple-negative breast cancer cells in vitro and in vivo [ 26 ]. Since emergence of resistance to current therapeutics remains a formidable problem in effective treatment and management of RCCs in clinic [ 5 – 7 ], we speculated whether CFM class of compounds would be effective inhibitors of RCC cells and to the extent, these compounds would be suitable to inhibit the resistant RCCs.…”
Section: Resultsmentioning
confidence: 99%
“…Structure and synthesis of the C4.16 compound have been previously described [16,40]. A stock solution of 50 mM of C4.16 was solubilized in dimethyl sulfoxide (DMSO) and stored at –20°C for further use.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured with ~70–80% confluence. We cultured Evr-res A498 cells to form 3D spheroid structure based on previously published methods [16,40]. Briefly, the cells were washed twice in 1 × PBS, trypsinized and pelleted the cells with 200 ×g centrifugation at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation